Women's Inferiority in the Novel RE: by Maman Suherman A Study of Feminist Literary Criticism - Setiawan Setiawan; Andi Tenri Sua; Andi Nurhabibi Marwil; Andi Srimularahmah (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to describe the inferiority of women in the novel RE: by Maman Suherman with a study of feminist literary criticism. This type of research uses qualitative research with analytical descriptive methods. The data in this research is in the form of novel text excerpts in the form of words, phrases, clauses, sentences and discourses in which women's inferiority is expressed in the form of physical and sexual violence. The data source in this research is written data contained in the novel RE: by Maman Suherman (2014). The instrument in this research is the researcher as the main instrument. The data collection technique used in this research is content analysis of documents and archives. Triangulation is a technique for checking the validity of data that uses something other than the data for checking purposes or as a comparison of the data.The research results found that there was inferiority towards women in the form of physical violence and sexual violence experienced by RE characters and their friends.